2012
DOI: 10.1155/2012/201502
|View full text |Cite
|
Sign up to set email alerts
|

The Human Mandible and the Origins of Speech

Abstract: Among the unique traits of human mandibles is the finding of relatively greater utilization of cortical bone with respect to other hominoids. The functional significance of this trait is not plausibly linked to masticatory demands given the diminution of the masticatory musculature in human evolution and the behavioral universal of extraoral food preparation in recent humans. Similarly, the presence of more mandibular bone is not a correlated effect of systemic skeletal robusticity, since gracilization of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 96 publications
(136 reference statements)
2
28
0
Order By: Relevance
“…Ichim et al (2006), on the other hand, found that there were no differences in symphyseal strains in their chinned and non-chinned models leading them to conclude that the chin is likely unrelated to the functional demands of mastication. This latter result is consistent with a recent analysis by Daegling (2012), who was unable to document a meaningful correlation between chin prominence and symphyseal bending moment arm lengths in modern human samples.…”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…Ichim et al (2006), on the other hand, found that there were no differences in symphyseal strains in their chinned and non-chinned models leading them to conclude that the chin is likely unrelated to the functional demands of mastication. This latter result is consistent with a recent analysis by Daegling (2012), who was unable to document a meaningful correlation between chin prominence and symphyseal bending moment arm lengths in modern human samples.…”
Section: Introductionsupporting
confidence: 92%
“…As such, the degree to which a prominent chin may act to resist mechanical stresses during mastication may simply be a secondary consequence of differential jaw growth and associated changes in symphyseal form (e.g. Gr€ oning et al 2011;Daegling, 2012), rather than being a primary causal mechanism. Indeed, although a bony chin may act to increase resistance to bending, mandibular strains in humans are likely low to begin with as a result of an evolutionary reduction in the size of the masticatory apparatus and an increased reliance on technocultural adaptation and extraoral processing.…”
Section: Introductionmentioning
confidence: 99%
“…The factors that might have influenced the presence of a protruding mental region in modern humans have been debated with regard to tooth size reduction (Hrdlicka, 1911;Riesenfeld, 1969), speech articulation (Walkhoff, 1904;DuBrul & Sicher, 1954;Ichim et al 2007;Daegling, 2012) and masticatory stresses (Howells, 1959;White, 1977;Daegling, 1993Daegling, , 2012Dobson & Trinkaus, 2002;Ichim et al 2006;Grö ning et al 2011). DuBrul & Sicher (1954) and Enlow (1990) have suggested that the prominence of the mental region is influenced by the development of the vocal tract musculature and the spatial restriction at the back of the oral cavity.…”
Section: Introductionmentioning
confidence: 99%
“…These muscular structures act as significant contributors to the positioning and orientation of the anterior teeth through bone remodeling, which ultimately shapes the prominence of the mental region . Furthermore, changes in the magnitude and frequency of strain produced by various muscle groups associated with speech production also play a significant role in shaping the mental region . High‐frequency and low‐magnitude forces associated with speech production, significant increases in the trabecular density, and bone volume may account for the significant postnatal development of this region .…”
Section: Discussionmentioning
confidence: 99%